The association between body roundness index and osteoporosis in American adults: analysis from NHANES dataset - Zhang, Xunmeng; Liang, Jiarong; Luo, Hong; Zhang, Huanhuan; Xiang, Jing; Guo, Lianjin; Zhu, Xuemin (Frontiers in Nutrition, 2024)
Background An innovative way to quantify obesity that appropriately captures levels of visceral and body fat is the Body Roundness Index (BRI). The purpose of this study is to look at the relationship between BRI and osteoporosis (OP) in adult Americans. Methods This study utilized data from the National Health and Nutrition Examination Survey (NHANES) collected between 2007 and 2018. NHANES is a research program designed to assess the health and nutritional status of adults and children in the United States. It conducts surveys focusing on various populations and health-related topics. Logistic regression analysis was employed to investigate the relationship between BRI and OP, adjusting for various covariates. BRI was categorized into four levels to further explore the association trends between different BRI levels and OP, enhancing the robustness of the results. Using restricted cubic spline (RCS) analysis, the dose–response relationship between BRI and OP was illustrated. Subgroup analyses were also carried out to evaluate the consistency and robustness of the findings. Results This study included 8,899 participants aged 50 years and older, among whom 763 had OP. BRI and the prevalence of OP were inversely correlated in the fully adjusted model (OR = 0.79, 95% CI: 0.69–0.86). The prevalence of OP considerably reduced with higher BRI levels when BRI was converted from a continuous to a categorical variable in comparison to the lowest BRI quartile. RCS analysis revealed an L-shaped negative correlation between BRI and OP prevalence, with a threshold effect analysis identifying a breakpoint at BRI = 5.29. Each unit increase in BRI to the left of this breakpoint was linked to a 36% decrease in the probability of OP (OR = 0.64, 95% CI: 0.57–0.72). Based on stratified factor subgroup analyses, it was shown that the negative correlation between BRI and OP persisted. Conclusion In a large, representative sample of American adults, this study identified a significant negative correlation between BRI and the prevalence of OP. Specifically, as BRI increases, the prevalence of osteoporosis decreases. Maintaining an appropriate and healthy BRI level may play a critical role in the prevention of osteoporosis. Therefore, regular monitoring of BRI and the adoption of appropriate health measures are essential for reducing the risk of osteoporosis.